A cross-sectional study to assess the health hygiene status of school children in urban field practice area, Bangalore Medical College And Research Institute, Bengaluru - Ambiger, Netravati; Ranganath, T. S.; Kavitha, M.; Padmini, D. B. (International Journal Of Community Medicine And Public Health, 2018)
Background: A large fraction of the world’s illness and death is attributable to communicable diseases. This is especially notable in developing countries where acute respiratory and intestinal infections are the primary causes of morbidity and mortality among young children. Objective of the study was to assess the basic hygiene practices among primary school children in urban field practice area, BMC&RI. Methods: A cross sectional study was carried out during September and October 2016 on a total of 125 school children to assess the level of basic hygiene practices in Urban field practice area, BMCRI. A Random sampling technique was used and pre tested and semi structured questionnaire was read out to the participants during face to face interview and sufficient time was given to the subjects to respond, without probing the answer. Results: Among 125 students, 54% were female and 46% were male.53.6% students take bath on alternate days, 88% students wash their feet daily, and 76% students change their cloth daily.75.2% students had h/o head lice and 57.6% students had h/o dental caries. Conclusions: Out of 125, 56.8% of students have excellent hygiene, 42.4% of students have very good hygiene and 0.8% students have good hygiene.